Adaptasi dan Validitas Konstruk Adaptive Performance Scale (APS) di Indonesia - Eureka Maharani J. Nasution; Bagus Wicaksono (Jurnal Ilmu Perilaku, 2025)
Adaptive performance reflects an individual's ability to adapt to changes in the work environment. Although the Adaptive Performance Scale (APS) has been widely used, no version has been adapted into Indonesian. This study aims to evaluate the validity and reliability of the Adaptive Performance Scale (APS), developed by Charbonnier-Voirin & Roussel (2012) and adapted for use in Indonesia, as a tool for measuring individual adaptive performance within an organizational context. This research was conducted in two studies. In study 1, the translation process and content validity testing involved 4 translators, 5 expert reviewers, and 7 laypeople. Meanwhile, study 2 involved 322 employees in Indonesia (134 males; 188 females) aged between 18-58 years (mean age = 28.9 years; SD = 8.1), using purposive sampling technique. The entire adaptation process referred to the International Test Commission (ITS) Guidelines for Test Adaptation. Confirmatory Factor Analysis (CFA) was utilized to evaluate the measurement model. The results demonstrated that the APS fulfilled the model fit criteria as a multidimensional construct comprising five factors. The APS also demonstrated good reliability. Overall, this study shows that the APS is valid and reliable, making it suitable for measuring adaptive performance in Indonesia.